Endotracheal hamartoma case report: Two contrasting clinical presentations of a rare entity. (2017) - Hon, Curtis; O'Hara, Carl J.; Litle, Virginia R.
Highlights: Hamartomas are benign tumors that are rarely localized to the trachea. Symptoms often gradual, mimicking those of chronic obstructive pulmonary disease. Successful management of Endotracheal Hamartomas is feasible using a bronchoscopic approach. Etiology of endotracheal hamartomas is unknown. Early suspicion in patients with obstructive pulmonary symptoms can prevent easily avoidable fatal complications. Abstract: Introduction: The majority of tracheal tumors in adults are malignant. The finding of a benign tumor in the trachea is uncommon and endotracheal hamartomas are rare. Presentation of case: We report two cases presenting within six months at our institution. The first patient is a 67 year-old man who was found to have an asymptomatic endotracheal hamartoma on chest imaging for aortic valve replacement. The second patient is a 46 year-old man with an extensive continued tobacco use disorder and a known endotracheal lesion identified 8 years prior to intervention. Both patients were treated surgically and recovered without complications. Discussion: Identification of these lesions and timely management are necessary because without intervention, they can lead to fatal complications. Most symptoms of tracheal hamartoma result from mechanical obstruction with the earliest presenting symptom being dyspnea, but as evident in these two cases, they can have different presentations. Conclusion: We have found that endotracheal hamartoma has a tendency to present in Caucasian, male patients with a comorbidity of respiratory disease and variable smoking history, but it can also present in asymptomatic patients with no significant smoking history.